Gene Chip Technology Used in the Detection of HPV Infection in Esophageal Cancer of Kazakh Chinese in Xinjiang Province - 陈卫刚 杨春梅 徐丽红 张宁 刘晓燕 马云贵 霍晓玲 韩玉胜 田德安 郑勇 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
Summary： This study was aimed to screen human papillomavirus （HPV） types associated with esophageal squamous cell carcinoma of Kazakh in Xinjiang using the gene chip technique and study the clinical significance of this application. The DNAs were collected from esophageal squamous cell carcinoma tissues and healthy esophageal mucosa of Kazakh adults in Xinjiang, and amplified firstly using HPV MY09/11 and then using HPV G5＋/6＋ to screen positive HPV specimens. These positive specimens were further detected by the gene chip technique to screen highly pathogenic HPV types. After determination with nested PCR amplification with HPV MY09/ll and G5＋/6＋, the infection rate of HPV was 66.67% in the esophageal squamous cell carcinoma group and 12.12% in the healthy control group. By testing the positive HPV specimens from the esophageal squamous cell carcinoma group, the infection rate of HPV16 was 97.72% and the co-infection rate of HPV16 and HPV18 was 2.27%. HPV16 infection may be involved in the development of esophageal squamous cell carcinoma in Xinjiang Hazakh adults.